THE EFFECT OF PERSONALITY CHARACTERISTICS OF HEALTHCARE WORKERS ON THEIR PERCEPTIONS OF ORGANIZATIONAL SUPPORT AND ORGANIZATIONAL TRUST - Tekin Sancar; Fuat Yalman (İşletme Bilimi Dergisi)
Aim: The main purpose of this study is to determine the effect of the personality characteristics of healthcare workers on their perceptions of organizational support and organizational trust. Method: The population of the research consisted of the employees of the private hospital providing secondary care in three different regions in Istanbul. The convenience sampling method was preferred in the study. The data were collected using the online questionnaire technique. The total number of questionnaires that were evaluated and used in the data analysis is 510. SPSS 23 and AMOS 26 package programs were used to analyze the data. Descriptive statistics, multiple linear regression analysis, and structural equation modeling were applied to the data. Findings: The findings obtained with the structural equation analysis showed that the construct validity of the model was provided. The direct causal effect of the personality traits of health workers on their perceptions of organizational support is positive, and the effect level is 0.122; On the other hand, it has been determined that the direct causal effect on organizational trust perceptions is positive, and the effect level is 0.225. Results: According to the results obtained from the regression analysis, it is seen that the high level of extraversion, responsibility, and openness characteristics of health workers positively affected their perceptions of organizational support. Therefore, healthcare professionals who are more extrovert, adaptable, and responsible show higher organizational support and organizational trust. It is suggested that personality traits being compatible with the organization may have a positive effect on outputs such as employee performance, job satisfaction, commitment, and motivation, and the study should be expanded in this direction.